Asazi ukuthi iyozala nkomoni: Robert Mangaliso Sobukwe’s historical imagination of the future - Delport, Terblanche (PINS-Psychology in Society, 2024)
This study will attempt to foreground the various underlying facets of Sobukwe’s historical imagination and social philosophy through a close reading of his speeches and writings. It will be shown how Sobukwe’s thought contains important observations for the study of identity, culture, history, and society; all concepts that are also of great importance to the field of psychosocial studies. The specific psychosocial dimension of Sobukwe’s thought lies in an attention to the role of the historical imagination, what we can tentatively name a historical form of consciousness. This is a form of consciousness that stands in opposition to and looks beyond what is confined and prescribed as the current and its possibilities. The interrelationship between psychological and political liberation will be explored and expanded upon through a focus on the role that history plays in both. It will be shown how Sobukwe, together with other intellectuals and politicians associated with Pan-Africanism and African Nationalism, mobilised history as a theatre of struggle that tied together the realms of the psychological and the political in the quest for African liberation.